Adaptation Study of the Problem Solving Inventory on the Turkish Athlete Population - Bulent Okan Micoogullari; Ridvan Ekmekci (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
The aim of this study was to examine the reliability and validity of Problem solving inventory (PSI) with Turkish athletes. The PSI was designed to clarify utility of problem-solving constructs across sports environment and thus facilitate the development of more comprehensive acknowledges about problem solving and mental health. The subjects were 204 males and 109 females totaling 313 athletes. Participants voluntarily completed the 32 item problem solving inventory. Afterwards, exploratory factor analysis (EFA) and confi rmatory factor analysis (CFA) were undertaken. EFA results yielded a satisfactory three-factor solution, the same as the English version. Cronbach alpha (α) reliability indices for the respective subscales were as follows: problem solving confi dence (PSC) (.69), approach and avoidance (AA) (.73), and personal control (PC) (.68). The PSI explained 66% of the total variances. Moreover, CFA results provided the fi t indices as Chi-Square (X²)=912.8, df=461, X²/df=1.98, Root Mean Square Error Approximation (RMSEA)=.07, Comparative Fit Index (CFI)=.93, Goodness of Fit Index (GFI)=.92, Normed Fit Index (NFI)=.90, Non Normed Fit Index (NFI)=.89 with 32 items and 3 sub-dimensions. The fi t indices of the PSI in relation to EFA and CFA were at an acceptable level. The original 3-factor solution was supported by the Turkish athlete subjects. Results of the study introduced that the Turkish version of the Problem Solving Inventory is a valid and reliable measurement for Turkish athletes.